Developing the "Permata" Educational Game Application to Enhance Currency Understanding for Students with Mild Disabilities at a Special Needs School in Sawahlunto - Mega Iswari; Ahmad Zikri; Yosa Nasti; Zulmiyetri (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
This study aims to develop and evaluate the PERMATA educational game application, a digital learning medium designed to enhance students' understanding of currency among those with mild intellectual disabilities at a YKB Special Needs School. The research adopted the Research and Development (R&D) methodology, following the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Media, material, and language experts assessed the application's validity. Practicality was tested with teachers and students, while effectiveness was measured using a pre-test and post-test design with 26 students to gauge improvement in their current comprehension. The validation results confirmed the application's high quality, with an average validity score of 92% (very valid). Practicality tests yielded scores of 93% from teachers and 95% from students (very practical). The effectiveness test demonstrated a significant increase in learning outcomes, with an average score of 85.8% (very effective), indicating that the application successfully improved students' understanding of currency. This study addresses a critical gap in special education by developing a tailored digital game that specifically targets financial literacy for students with mild intellectual disabilities. The PERMATA application is a novel, validated tool that serves as a viable, practical, and compelling interactive medium for enhancing essential life skills, making a significant contribution to inclusive, technology-driven education. Keywords: educational game, currency understanding, mild intellectual disability, special needs education